Scaling up Resource Efficiency and Cleaner Production for an Sustainable Industrial Development. (2018) - Szilagyi, Aida; Mocan, Marian
Abstract: Resource Efficiency and Cleaner Production (RECP) is a globally proven approach to improve productivity and reduce environmental impact of the enterprises. Application of RECP is beneficial for enterprises, in particular SME's, contributing to enhancing their productivity and competitiveness; for the environment by lowering the impact of their operations, and for people, by decreasing the risks to workers and communities (UNIDO, 2015). Greening up the economies, the major global trend nowadays, could become reality by focusing on the existing industries and by supporting an significant number of enterprises, in particular SME's, to increase resource efficiency and productivity while lowering their impact on the environment. Implementing RECP requires a systematic and continuous approach for the identification and evaluation of the existing inefficiencies, addressing them by applying "standard practices" to all waste and emissions causes and process inefficiencies and monitoring the enterprises level results; the method usually implies elaboration of quit complex materials and energy balances, and laborious feasibility analyses, activities usually performed with technical support from RECP experts. The question raised in the last years was how to increase the number of companies implementing RECP and how to sustain and mainstream RECP. Solutions are proposed to intensify application of RECP methods, practices and techniques and innovative approaches are used to facilitate the expansion of RECP application and transfer of existing experiences and best practices to a larger number of enterprises.